L’âme des machines dans The Ghost in the Shell - Bounthavy Suvilay (ReS Futurae)
In Ghost in the Shell, Masamune Shirow aimed to publicize the concept of holons continuing the reasoning of Arthur Koestler in order to apply it to the computer. But by using the medium of comic book, his message was profoundly changed. The comics are an art of the ellipse in which the reader fills the gap between the cases and creates the diegetic universe. But manga as it is practiced in the ecosystem of the Japanese media does not lend itself to abstraction. By analyzing the various mechanisms put in place to ensure the proper transmission of information, this paper intends to show how it is possible to represent a technological element which escapes the human senses. The mangaka supplements his fiction with a metatext that constantly interrupts the reading of the narration. He also tries to get his message graphically using abstractions or figures referring to religion. Since his footnotes are perceived as marginal, most readers have been more focused on the investigations of the Section 9 rather than on Shirow’s philosophical comments. Numerous Ghost in the Shell adaptations in the media mix environment underscore the partial failure of Shirow’s initial project, each creator giving his version of the diegetic world and developing incompatible parallel universes. But they have a similar pattern to the reference intermedia even invent a work cited.